2021
DOI: 10.1016/j.virusres.2020.198246
|View full text |Cite
|
Sign up to set email alerts
|

The DHODH inhibitor PTC299 arrests SARS-CoV-2 replication and suppresses induction of inflammatory cytokines

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has created an urgent need for therapeutics that inhibit the SARS− COV-2 virus and suppress the fulminant inflammation characteristic of advanced illness. Here, we describe the anti− COVID-19 potential of PTC299, an orally bioavailable compound that is a potent inhibitor of dihydroorotate dehydrogenase (DHODH), the rate-limiting enzyme of the de novo pyrimidine nucleotide biosynthesis pathway. In tissue culture, PTC299 manifests robust, dose-dependent, and DHODH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 47 publications
(72 reference statements)
6
48
0
1
Order By: Relevance
“…In conclusion, our study while confirming along with others recent reports (12,18) hDHODH as a noteworthy target to inhibit SARS-CoV-2 infection (10,19), highlights MEDS433 as an attractive candidate to develop HTA for COVID-19. MEDS433 in fact performs better than brequinar for both antiviral potency and SI (this study and 16), and its safety profile is superior to that of PTC299 (12). Therefore, the potent in vitro anti-SARS-CoV-2 activity of MEDS433 and its valuable drug-like profile, support further studies to validate its therapeutic efficacy in preclinical animal models of COVID-19.…”
Section: Main Textsupporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, our study while confirming along with others recent reports (12,18) hDHODH as a noteworthy target to inhibit SARS-CoV-2 infection (10,19), highlights MEDS433 as an attractive candidate to develop HTA for COVID-19. MEDS433 in fact performs better than brequinar for both antiviral potency and SI (this study and 16), and its safety profile is superior to that of PTC299 (12). Therefore, the potent in vitro anti-SARS-CoV-2 activity of MEDS433 and its valuable drug-like profile, support further studies to validate its therapeutic efficacy in preclinical animal models of COVID-19.…”
Section: Main Textsupporting
confidence: 91%
“…Given its critical role, hDHODH is considered an emerging target of choice for the development of HTA against SARS-CoV-2 (10). In this regard, two potent hDHODH inhibitors just entered in Phase II clinical trials for COVID-19: brequinar (11) (NCT04425252), and PTC299 (12) (NCT04439071). However, these drug candidates suffer of toxicity issues that slowed down their earlier clinical pathway on other therapeutic applications (13, 14).…”
Section: Main Textmentioning
confidence: 99%
“…Also, this drug has been found to suppress the release of important cytokines that play a role in ARDS (IL-6, IL17) and vascular endothelial growth factor (VEGF). In addition, a clinical study started on July 9 to investigate the effect of PTC299 on COVID19 (Clinical Code: NCT04439071) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new DHODH inhibitors discovered in a number of studies have been demonstrated to suppress both virus infection and cytokine storm [ 33 , 36 , 37 ]. It has been reported that the clinical trials of IMU-838 and PCT299 against COVID19 are ongoing (ClinicalTrials Code: NCT04379271, ClinicalTrials Code: NCT04439071).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dihydroorotate dehydrogenase (DHODH) [ 34 ] was considered as drug target for SARS-CoV-2 treatment [ 35 ]. The DHODH Inhibitor ICV617 is a highly potent inhibitor of SARS-CoV-2 replication (EC 50 = 1.96 nM) [ 36 ]. ICV618 can prevent infection by SARS-CoV-2 as an inhibitor of PIKfyve kinase (IC 50 = 10 nM) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%